Hydrogen-assisted post-growth substitution of tellurium into molybdenum disulfide monolayers with tunable compositions. (16th February 2018) - Yin, Guoli; Zhu, Dancheng; Lv, Danhui; Hashemi, Arsalan; Fei, Zhen; Lin, Fang; Krasheninnikov, Arkady V; Zhang, Ze; Komsa, Hannu-Pekka; Jin, Chuanhong
Abstract: Herein we report the successful doping of tellurium (Te) into molybdenum disulfide (MoS2 ) monolayers to form MoS2 x Te2(1− x ) alloy with variable compositions via a hydrogen-assisted post-growth chemical vapor deposition process. It is confirmed that H2 plays an indispensable role in the Te substitution into as-grown MoS2 monolayers. Atomic-resolution transmission electron microscopy allows us to determine the lattice sites and the concentration of introduced Te atoms. At a relatively low concentration, tellurium is only substituted in the sulfur sublattice to form monolayer MoS2(1− x ) Te2 x alloy, while with increasing Te concentration (up to ∼27.6% achieved in this study), local regions with enriched tellurium, large structural distortions, and obvious sulfur deficiency are observed. Statistical analysis of the Te distribution indicates the random substitution. Density functional theory calculations are used to investigate the stability of the alloy structures and their electronic properties. Comparison with experimental results indicate that the samples are unstrained and the Te atoms are predominantly substituted in the top S sublattice. Importantly, such ultimately thin Janus structure of MoS2(1− x ) Te2 x exhibits properties that are distinct from their constituents. We believe our results will inspire further exploration of the versatile properties of asymmetric 2D TMD alloys.